GEOGRAPHIC AND ALTITUDINAL DISTRIBUTION OF SNAKES OF THE FAMILY BOIDAE IN THE STATE OF BAHIA, NORTHEASTERN BRAZIL - Pinto-Coelho, Daniela; Hamdan, Breno; Lira-da-Silva, Rejâne M. (Revista Nordestina de Zoologia, 2020)
Documenting the current spatial distribution of species is one of the first steps for understanding the patterns and associated processes of biological evolution. We aim to map the geographical and altitudinal distribution, as well as identifying the predominant ecoregions of the presence of all species of snakes of the family Boidae in the state of Bahia, in northeastern Brazil. Thus, we expected to help describe and understand the patterns of the geographical distribution of Boidae species in South America. We analysed data from herpetological collections and literature to perform the distribution maps of Boidae species. Our results reported six species of Boidae in altitudes varying from four to 1,011 m above sea level, inhabiting the Atlantic coastal restingas, Atlantic dry forests, Bahia coastal forests, Bahia interior forests, Caatinga, Cerrado, Pernambuco interior forests, and campos rupestres montane savanna. No species widespread in all ecoregions though. The Brazilians herpetological collections consulted do not have a good representative sample for Boidae which may prejudice further biogeographic and evolutionary studies.